Questions of aesthetics and poetics of folk art in folklore the herritage of Ivan Franko (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the article is probed scientific understanding of I.Franko aesthetically fea-tures ancient time (beforemyfological), new time (mythological), newest time (aftermyfological) the stages of development of the folk thinking and forming on this basis of poetic texts of different folk-lore genres and also value of ideas and conclusions of I.Frankо for forming of national bases of the modern Ukrainian ethnology.
Keywords: aesthetics; fetishism; animism; myth; new world view